REVIEW OF THE MONOGRAPH OF YU. YU. KLYTCHNIKOV NORTHERN CAUCASUS: OLD ISSUES IN NEW DIMENSION (HISTORICAL AND POLITICAL ESSAYS)» // under edition and with a foreword by Prof. S. L. Dudarev. Pyatigorsk: VO PSLU, 2016. 99 р - Tatyana Alexandrovna Shebzukhova (Современная наука и инновации, 2022)
Review of the competent and rare historical-political study of the problems of the North Caucasus in the modern time, accompanied by a variety of specific and valid links.